1965
DOI: 10.1177/004051756503500305
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Evaluation of Actinic Degradation of Fibers

Abstract: A procedure giving reproducible data has been devised for the preparation, exposure, and testing of yarns in fabric form for resistance to actinic degradation. Effects of season, test location, and sample presentation have been considered. It has been shown that ultraviolet radiation is a more useful index of exposure than total incident radiation. It is suggested that the cyclical seasonal variation of ozone in the upper atmosphere is responsible for the observed seasonal variations in ultraviolet radiation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1966
1966
2010
2010

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…For example, it has long been recognized that dominant failure mode for nominally identical specimens exposed for the same duration and at the same time often changes from one environment to another [Scott, 1983] and that the rankings of outdoor exposure results do not agree for coated specimens exposed 1) at the same site and at the same time of year, but in different years [Grinsfelder, 1967] 2) at the same site, but at different times [Stieg, 1975;Ellinger, 1977;Lindberg, 1982;Stieg, 1966;Rosendahl, 1976;Grossman, 1993;Greathouse and Wessel, 1954;Morse, 1964;Singleton et al, 1965;Grinsfelder, 1967;Rosato, 1968;Mitton et al, 1971;Gaines et al, 1977;Scott, 1977] 3) at the same site, same year, and the same time of year, but for different durations [Reinhart, 1958], and 4) at different sites, but at the same time of the same year [Stieg, 1975;Kamal, 1966;Hoffman and Saracz, 1969;Morse, 1964;Singleton et al, 1965]. In fact, no study was found claiming that outdoor exposure results are reproducible.…”
Section: Characterization Of Outdoor Exposure Environmentsmentioning
confidence: 99%
“…For example, it has long been recognized that dominant failure mode for nominally identical specimens exposed for the same duration and at the same time often changes from one environment to another [Scott, 1983] and that the rankings of outdoor exposure results do not agree for coated specimens exposed 1) at the same site and at the same time of year, but in different years [Grinsfelder, 1967] 2) at the same site, but at different times [Stieg, 1975;Ellinger, 1977;Lindberg, 1982;Stieg, 1966;Rosendahl, 1976;Grossman, 1993;Greathouse and Wessel, 1954;Morse, 1964;Singleton et al, 1965;Grinsfelder, 1967;Rosato, 1968;Mitton et al, 1971;Gaines et al, 1977;Scott, 1977] 3) at the same site, same year, and the same time of year, but for different durations [Reinhart, 1958], and 4) at different sites, but at the same time of the same year [Stieg, 1975;Kamal, 1966;Hoffman and Saracz, 1969;Morse, 1964;Singleton et al, 1965]. In fact, no study was found claiming that outdoor exposure results are reproducible.…”
Section: Characterization Of Outdoor Exposure Environmentsmentioning
confidence: 99%
“…4 This is because the exposure times are shorter during the winter months (shorter days) and the UV content of winter sunlight is between one-third and one-thirtieth that of summer sunlight. 5,6 Yearly variations can change the absolute rates of degradation by a factor of two. 7,8 Thermal variations across a single exposure rack can lead to significant variability in gloss retention and chalking results.…”
Section: Correlation With Exterior Weathering Resultsmentioning
confidence: 99%
“…Furthermore, the relationships of chemical changes in the structure of a polymeric material to c hanges in mechanical properties have not been fully established. For this reason it is difficult to predict quantitatively how initial chemical changes in the properties [45]. It is, therefore, understandable when an increasing number of papers are devoted to the quantitative study of the photochemical processes that occur in dyed materials [2, 3, 11-13; 32, 48-51].…”
Section: Concept Of Light Stabilitymentioning
confidence: 99%